Presence of SARS-CoV-2 and Its Entry Factors in Oral Tissues and Cells: A Systematic Review - Marco Felipe Salas Orozco; Nereyda Niño-Martínez; Gabriel-Alejandro Martínez-Castañón; Nuria Patiño Marín; Carolina Sámano Valencia; Farid Alonso Dipp Velázquez; Paulina del Carmen Sosa Munguía; Miguel Angel Casillas Santana (Medicina, 2021)
Background and Objectives: The aim of this systematic review is to summarize the current data about the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its entry factors in oral tissues and cells. Materials and Methods: This systematic review was carried out based on the Preferred Reporting Items for a Systematic Review and Meta-Analysis (PRISMA). Three databases were analyzed (Pubmed, Web of science and Scopus) by three independent researchers. From the 18 identified studies, 10 of them met the inclusion criteria. The presence of SARS-CoV-2 or its entry factors (angiotensin-converting enzyme II (ACE2), transmembrane serine proteases (TMPRSS), and furin) was analyzed in these 10 studies during the pandemic. Results: ACE2 expression was analyzed in 9 of the 10 studies. ACE2 is expressed mainly in the tongue, oral mucosa, salivary glands and epithelial cells. The expression of the TMPRSS2 gene or protein was analyzed in 6 studies. These studies reported that the expression of TMPRSS2 was mainly in the salivary glands, tongue, sulcular epithelium and oral mucosa; as well as in cells of the salivary glands (ductal, acinar and myoepithelial cells) and the tongue (the spinous-based cell layer, horny layer and the epithelial surface). Other TMPRSS were also reported. The expression of TMPRSS3, TMPRSS4, TMPRSS5, TMPRSS7 and TMPRSS11D was reported mainly in salivary glands and in epithelial-type cells. Furan expression was analyzed in three studies. The expression of furin was detected mainly in epithelial cells of the tongue. A variety of methods were used to carry out the detection of SARS-CoV-2 or its input molecules. Conclusions: These results show that SARS-CoV-2 can infect a wide variety of oral tissues and cells, and that together with the theories dedicated to explaining the oral symptoms present in SARS-CoV-2 positive patients, it provides us with a good scientific basis for understanding the virus infection in the oral cavity and its consequences.